Intensity interferometry for the 21st century - Horch, Elliott P.; van Belle, G. T.; Genet, R. M.; Holenstein, B. D. (Journal of Astronomical Instrumentation, 2013)
Advances in detector technology and electronic timing capabilities in recent years have resulted in a new opportunity for ultra-high resolution in astronomy using intensity interferometry. We have been working with this technology and describe here the potential as we see it. Two separate opportunities exist at present: The use of Single Photon Avalanche Diode (SPAD) detectors with existing research-grade telescopes and photomultipliers coupled with light bucket telescopes. In the future, there may also be potential for space-based intensity interferometry. While intensity interferometry is not likely to replace amplitude-based interferometry, it does have certain advantages in terms of portability, use of large baselines, narrow-band imaging, and imaging in the blue. We see a new possibility for its use particularly in stellar astrophysics for these reasons. © 2013 World Scientific Publishing Company.
9 citations (Crossref) [2023-10-31] Citation Key Alias: pop00124
Keywords: Instrumentation: Interferometers; dept.phy; high angular resolution; techniques: Interferometric

Spitzer observations of gj 3470 b: a very low-density neptune-size planet orbiting a metal-rich m dwarf* - Demory, Brice-Olivier; Torres, Guillermo; Neves, V.; Rogers, Leslie A.; Gillon, Michaël; Horch, Elliott P.; Sullivan, Peter W.; Bonfils, Xavier; Delfosse, Xavier; Forveille, Thierry; Lovis, Christophe; Mayor, Michel; et al. (The Astrophysical Journal, 2013)
We present Spitzer/IRAC 4.5 μm transit photometry of GJ 3470 b, a Neptune-size planet orbiting an M1.5 dwarf star with a 3.3 day period recently discovered in the course of the HARPS M-dwarf survey. We refine the stellar parameters by employing purely empirical mass-luminosity and surface brightness relations constrained by our updated value for the mean stellar density, and additional information from new near-infrared spectroscopic observations. We derive a stellar mass of and a radius of of M* = 0.539 +0.047-0.043 M⊙ and a radius of R* = 0.568+0.037-0.031 R⊙. We determine the host star of GJ 3470 b to be metal-rich, with a metallicity of [Fe/H] = +0.20 ± 0.10 and an effective temperature of Teff = 3600 ± 100 K. The revised stellar parameters yield a planetary radius Rp= 4.83+0.22-0.21 R⊕that is 13% larger than the value previously reported in the literature. We find a planetary mass M p= 13.9+1.5-1.4 M⊕ that translates to a very low planetary density, ρp = 0.72+0.13 -0.12 g cm-3, which is 33% smaller than the original value. With a mean density half of that of GJ 436 b, GJ 3470 b is an example of a very low-density low-mass planet, similar to Kepler-11 d, Kepler-11 e, and Kepler-18 c, but orbiting a much brighter nearby star that is more conducive to follow-up studies. © 2013. The American Astronomical Society. All rights reserved.
29 citations (Crossref) [2023-10-31] Citation Key Alias: pop00035 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (GJ 3470); techniques: photometric; techniques: spectroscopic

Exoplanet characterization by proxy: A transiting 2.15 r ⊕ planet near the habitable zone of the late K dwarf Kepler-61 - Ballard, Sarah; Charbonneau, David; Fressin, Francois; Torres, Guillermo; Irwin, Jonathan; Desert, Jean-Michel; Newton, Elisabeth; Mann, Andrew W.; Ciardi, David R.; Crepp, Justin R.; Henze, Christopher E.; Bryson, Stephen T.; et al. (The Astrophysical Journal, 2013)
We present the validation and characterization of Kepler-61b: a 2.15 R ⊕ planet orbiting near the inner edge of the habitable zone of a low-mass star. Our characterization of the host star Kepler-61 is based upon a comparison with a set of spectroscopically similar stars with directly measured radii and temperatures. We apply a stellar prior drawn from the weighted mean of these properties, in tandem with the Kepler photometry, to infer a planetary radius for Kepler-61b of 2.15 ± 0.13 R ⊕ and an equilibrium temperature of 273 ± 13 K (given its period of 59.87756 ± 0.00020 days and assuming a planetary albedo of 0.3). The technique of leveraging the physical properties of nearby “proxy” stars allows for an independent check on stellar characterization via the traditional measurements with stellar spectra and evolutionary models. In this case, such a check had implications for the putative habitability of Kepler-61b: the planet is 10% warmer and larger than inferred from K-band spectral characterization. From the Kepler photometry, we estimate a stellar rotation period of 36 days, which implies a stellar age of >1 Gyr. We summarize the evidence for the planetary nature of the Kepler-61 transit signal, which we conclude is 30,000 times more likely to be due to a planet than a blend scenario. Finally, we discuss possible compositions for Kepler-61b with a comparison to theoretical models as well as to known exoplanets with similar radii and dynamically measured masses.
33 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/071-947-168-650-048, pop00052 tex.type: [object Object]
Keywords: dept.phy; eclipses; planetary systems; stars: individual (Kepler-61; KOI 1361; KIC 6960913)

The same frequency of planets inside and outside open clusters of stars. - Meibom, Soren; Torres, Guillermo; Fressin, Francois; Latham, David; Rowe, Jason; Ciardi, David; Bryson, Steven; Rogers, Leslie; Henze, Christopher; Janes, Kenneth; Barnes, Sydney; Marcy, Geoffrey; et al. (Nature, 2013)
: Most stars and their planets form in open clusters. Over 95 per cent of such clusters have stellar densities too low (less than a hundred stars per cubic parsec) to withstand internal and external dynamical stresses and fall apart within a few hundred million years 1. Older open clusters have survived by virtue of being richer and denser in stars (1,000 to 10,000 per cubic parsec) when they formed. Such clusters represent a stellar environment very different from the birthplace of the Sun and other planet-hosting field stars. So far more than 800 planets have been found around Sun-like stars in the field 2. The field planets are usually the size of Neptune or smaller 3,4,5. In contrast, only four planets have been found orbiting stars in open clusters 6,7,8, all with masses similar to or greater than that of Jupiter. Here we report observations of the transits of two Sun-like stars by planets smaller than Neptune in the billion-year-old open cluster NGC6811. This demonstrates that small planets can form and survive in a dense cluster environment, and implies that the frequency and properties of planets in open clusters are consistent with those of planets around field stars in the Galaxy., (C) 2013 Nature Publishing Group
84 citations (Crossref) [2023-10-31] Place: (C) 2013 Nature Publishing Group
Keywords: Jupiter; Neptune; article; astronomy; cluster analysis; dept.phy; environment; frequency analysis; planet; priority journal; simulation; sun; velocity

The mass of KOI-94d and a relation for planet radius, mass, and incident flux - Weiss, Lauren M.; Marcy, Geoffrey W.; Rowe, Jason F.; Howard, Andrew W.; Isaacson, Howard; Fortney, Jonathan J.; Miller, Neil; Demory, Brice-Olivier; Fischer, Debra A.; Adams, Elisabeth R.; Dupree, Andrea K.; Howell, Steve B.; et al. (The Astrophysical Journal, 2013)
We measure the mass of a modestly irradiated giant planet, KOI-94d. We wish to determine whether this planet, which is in a 22 day orbit and receives 2700 times as much incident flux as Jupiter, is as dense as Jupiter or rarefied like inflated hot Jupiters. KOI-94 also hosts at least three smaller transiting planets, all of which were detected by the Kepler mission. With 26 radial velocities of KOI-94 from the W. M. Keck Observatory and a simultaneous fit to the Kepler light curve, we measure the mass of the giant planet and determine that it is not inflated. Support for the planetary interpretation of the other three candidates comes from gravitational interactions through transit timing variations, the statistical robustness of multi-planet systems against false positives, and several lines of evidence that no other star resides within the photometric aperture. We report the properties of KOI-94b (M P = 10.5 ± 4.6 M ⊕, R P = 1.71 ± 0.16 R ⊕, P = 3.74 days), KOI-94c (M P = M ⊕, R P = 4.32 ± 0.41 R ⊕, P = 10.4 days), KOI-94d (M P = 106 ± 11 M ⊕, R P = 11.27 ± 1.06 R ⊕, P = 22.3 days), and KOI-94e (M P = M ⊕, R P = 6.56 ± 0.62 R ⊕, P = 54.3 days). The radial velocity analyses of KOI-94b and KOI-94e offer marginal (>2σ) mass detections, whereas the observations of KOI-94c offer only an upper limit to its mass. Using the KOI-94 system and other planets with published values for both mass and radius (138 exoplanets total, including 35 with M P < 150 M ⊕), we establish two fundamental planes for exoplanets that relate their mass, incident flux, and radius from a few Earth masses up to 13 Jupiter masses: (R P/R ⊕) = 1.78(M P/M ⊕)0.53(F/erg s–1 cm–2)–0.03 for M P < 150 M ⊕, and R P/R ⊕ = 2.45(M P/M ⊕)–0.039(F/erg s–1 cm–2)0.094 for M P > 150 M ⊕. These equations can be used to predict the radius or mass of a planet.
223 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-207-643-634-196, pop00005 tex.type: [object Object]
Keywords: dept.phy; planets and satellites: composition; techniques: photometric; techniques: spectroscopic

Kepler-63b: A giant planet in a polar orbit around a young sun-like star - Sanchis-Ojeda, Roberto; Winn, Joshua N.; Marcy, Geoffrey W.; Howard, Andrew W.; Isaacson, Howard; Johnson, John Asher; Torres, Guillermo; Albrecht, Simon; Campante, Tiago L.; Chaplin, William J.; Davies, Guy R.; Lund, Mikkel N.; et al. (The Astrophysical Journal, 2013)
We present the discovery and characterization of a giant planet orbiting the young Sun-like star Kepler-63 (KOI-63, M⊙Kp = 11.6, T eff = 5576 K, M⊙ = 0.98 M⊙). The planet transits every 9.43 days, with apparent depth variations and brightening anomalies caused by large starspots. The planet's radius is 6.1 ± 0.2 R ⊕, based on the transit light curve and the estimated stellar parameters. The planet's mass could not be measured with the existing radial-velocity data, due to the high level of stellar activity, but if we assume a circular orbit, then we can place a rough upper bound of 120 M ⊙⊕ (3σ). The host star has a high obliquity (ψ = 104°), based on the Rossiter-McLaughlin effect and an analysis of starspot-crossing events. This result is valuable because almost all previous obliquity measurements are for stars with more massive planets and shorter-period orbits. In addition, the polar orbit of the planet combined with an analysis of spot-crossing events reveals a large and persistent polar starspot. Such spots have previously been inferred using Doppler tomography, and predicted in simulations of magnetic activity of young Sun-like stars. © 2013. The American Astronomical Society. All rights reserved..
98 citations (Crossref) [2023-10-31] Citation Key Alias: pop00012 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: activity; stars: individual (Kepler-63); stars: rotation; starspots

A sub-Mercury-sized exoplanet. - Barclay, Thomas; Rowe, Jason; Lissauer, Jack; Huber, Daniel; Fressin, Francois; Howell, Steve; Bryson, Stephen; Chaplin, William; Desert, Jean-Michel; Lopez, Eric; Marcy, Geoffrey; Mullally, Fergal; et al. (Nature, 2013)
Since the discovery of the first exoplanets, it has been known that other planetary systems can look quite unlike our own. Until fairly recently, we have been able to probe only the upper range of the planet size distribution, and, since last year, to detect planets that are the size of Earth or somewhat smaller. Hitherto, no planets have been found that are smaller than those we see in the Solar System. Here we report a planet significantly smaller than Mercury. This tiny planet is the innermost of three that orbit the Sun-like host star, which we have designated Kepler-37. Owing to its extremely small size, similar to that of the Moon, and highly irradiated surface, the planet, Kepler-37b, is probably rocky with no atmosphere or water, similar to Mercury. © 2013 Macmillan Publishers Limited. All rights reserved.
161 citations (Crossref) [2023-10-31] Place: (C) 2013 Nature Publishing Group
Keywords: Earth; article; astronomy; atmosphere; dept.phy; irradiance; irradiation; moon; orbit determination; planetary surface; priority journal; size structure; solar system; sun; water